THE EFFORTS TO REDUCE PROSPERITY OF ASMA BRONCHIALE SUFFERS WITH YOGA GYM THERAPY - Fatsiwi Nunik Andari; Henni Febriawati; Mursid Wibowo (Avicenna: Jurnal Ilmiah, 2020)
Background: Asthma is an important chronic airway disease and a serious public health problem in various countries around the world. Asthma can be mild and does not interfere with activities, but can be permanent and interfere with activities and even daily activities. Productivity decreases due to absenteeism from work or school, and can lead to disability, thereby increasing productivity and decreasing quality of life. Methods: This research is a type of pre-experimental research with one group pre and post test design. Results: from 15 respondents before being given yoga exercise therapy there were 10 people (66.7%) who experienced chronic/ persistent asthma and 5 people (33.3%) who experienced episodic asthma. After giving yoga exercise therapy 6 times for 2 weeks, 3 people (20.0%) had chronic/ persistent asthma and 12 (80.0%) experienced episodic asthma. Based on the Wilcoxon test results obtained p value = 0.035 which means significant, so it can be concluded that yoga exercise therapy has an effect in reducing the recurrence of bronchial asthma sufferers in the working area of the Puskesmas Jalan Gedang, Bengkulu City.